Mengembangkan Keterampilan Sosial pada Anak Usia Dini: Studi tentang Komunitas di Daerah Tepi Sungai di Banjarmasin, Indonesia: Developing Social Skills in Early Childhood: A Study of Riverside Communities in Banjarmasin, Indonesia - Mariatul Kiptiah (Society, 2023)
This study investigates the development of early childhood social skills within Banjarmasin, Indonesia’s riverside communities. Social skills are crucial for the holistic development of children, facilitating better interaction, cooperation, and communication, which are essential for their personal and social growth. The unique socio-cultural dynamics of the riverside communities in Banjarmasin provide a distinctive environment for examining how these skills are nurtured. Utilizing a qualitative research design, this study aims to comprehend the socio-cultural context, identify specific social skills developed in early childhood, and assess the effectiveness of various community-based initiatives designed to foster these skills. The purposive sampling method was employed to select informants who could provide in-depth and relevant data. Data collection involved a combination of observations, semi-structured interviews, and active participation in community activities, ensuring a comprehensive understanding of the processes involved. The findings reveal that children in these communities enhance their social skills through a learning process deeply embedded in community values, emphasizing interaction and play. Community values, interactive learning, and cultural integration contribute to social skill development. Reinforcing community values such as togetherness, sharing, and mutual respect plays a critical role in socialization. Activities that promote interaction and play are central to developing social skills, with group activities such as cooperative games, creative arts, and storytelling sessions proving particularly effective in encouraging children to work together, communicate effectively, and build confidence. Additionally, the unique Banjar River culture significantly influences social behaviors, with activities specific to the river culture, including riverboat play and traditional storytelling, imparting cultural values and enhancing social competencies among children. The study concludes that leveraging the cultural uniqueness of the Banjar River communities is essential in building social skills in early childhood. Children in Banjarmasin’s riverside communities develop essential social skills more effectively by integrating community values and interactive learning within this cultural context. This research highlights the importance of culturally relevant approaches in early childhood education and suggests that similar methodologies could be adapted to other cultural settings to support social skill development.